Los imaginarios de internet: una aproximación crítica a los discursos hegemónicos en el ciberespacio - Sánchez Estellés, Isis; López Martín, Sara (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
The present paper has the aim of inquiring into the different social imaginaries which has appeared on the Internet since its beginning. Especially, we focus on the different social imaginaries about the concept of democracy. We have considered six relevant dimensions to the study of the concept of democracy: freedom, equality, partcipation security, rights and pluralism. We differentiate four social imaginaries (university/hackers; the market; Newest social movements and the State), working on the principle that each social imaginary has its particular discourse depending on how they understand the meaning of those dimensions (freedom, equlity...) and how they manifest their socio-political practice. Finally, we establish a comparative discourse analysis about the dimensions of the concept democracy to conclude with some ideas which encourage new research in this line.